PENGARUH PENGGUNAAN PHYPHOX BERBASIS INKUIRI TERBIMBING TERHADAP HASIL BELAJAR FISIKA MAHASISWA - Andre Valerius; Marianus Marianus; Ferdy Dungus (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2023)
The Physics learning process in this digital era still has many obstacles including limited laboratory equipment and media to facilitate physics learning. During the Covid-19 pandemic, using Phyphox as a physics learning media on Simple Harmonic Motion material is still lacking. This study aims to determine the effect of using the Phyphox application based on guided inquiry on student physics learning outcomes on simple pendulum material. This research is experimental research with one group pretest & posttest design. The population is physics students of Universitas Negeri Manado, and the sample is the Class of 2020. Analysis of the data obtained shows that there is an influence on the use of guided inquiry-based Phyphox on physics learning outcomes in physics student’s class of 2020. Based on the results of the average pre-test and post-test data, which increased from 59.33 -82.00. The t-test results obtained the value of tcount = 7.982 and tTabel = 1.761 with a significant level of 5%. therefore tcount < tTabel (-7.982 < 1.761) then: H0 is accepted and H1 is rejected. So, it can be concluded that with the application of the use of Phyphox applications can further improve student physics learning outcomes.